Assessment Methods in Medical Ultrasound Education - Höhne, Elena; Recker, Florian; Dietrich, Christoph Frank; Schäfer, Valentin Sebastian (Frontiers in Medicine, 2022)
Medical schools are increasingly incorporating ultrasound into undergraduate medical education. The global integration of ultrasound into teaching curricula and physical examination necessitates a strict evaluation of the technology's benefit and the reporting of results. Course structures and assessment instruments vary and there are no national or worldwide standards yet. This systematic literature review aims to provide an up-to-date overview of the various formats for assessing ultrasound skills. A review of literature using Embase, PubMed, Medline, Cochrane and Google Scholar was performed up to May 2021, while keywords were predetermined by the authors. Inclusion criteria were as follows: prospective as well as retrospective studies, observational or intervention studies, and studies outlining how medical students learn ultrasound. In this study, 101 articles from the literature search matched the inclusion criteria and were investigated. The most frequently used methods were objective structured clinical examinations (OSCE), multiple choice questions, and self-assessments via questionnaires while frequently more than one assessment method was applied. Determining which assessment method or combination is ideal to measure ultrasound competency remains a difficult task for the future, as does the development of an equitable education approach leading to reduced heterogeneity in curriculum design and students attaining equivalent skills.